Злочини проти громадського порядку: кримінологічна характеристика та питання запобігання Національною поліцією України - Денисов, С. Ф.; Denysov, S. F.; ORCID: https://orcid.org/0000-0002-1218-0016; Заїка, Д. Є.; Zaika, D. Ye.; ORCID: https://orcid.org/0000-0002-1300-3492 (Українська поліцеїстика: теорія, законодавство, практика. - 2022. - № 1(3). - С. 99-115, 2022)
Вироблено науково обґрунтовані рекомендації щодо запобігання злочинам проти громадського порядку силами Національної поліції України. Досліджено кількісно-якісні показники злочинів проти громадського порядку за останнє десятиріччя. Проаналізовано чинні міжнародні та вітчизняні нормативно-правові акти, матеріали наявних наукових досліджень. Розглянуто положення, що стосуються запобігання злочинам проти громадського порядку, надано рекомендації щодо вдосконалення нормативно-правового регулювання.

Ensuring public order in Ukraine is an important factor in the normal functioning of society. At the same time, the National Police face the need to detect and prevent hooliganism on a daily basis, and have repeatedly been involved in deterring mass riots or group disturbances. One of the components of developing an effective method of crime prevention of the study group is the analysis of basic criminological indicators, studying the identity of the offender and developing scientifically sound recommendations, which will further optimize the activities of structural units of the National Police of Ukraine. The article is devoted to the study of quantitative and qualitative indicators of crimes against public order over the past 10 years. Scientific research of the main criminological indicators of crimes against public order is one of the most successful methods for determining the nature and degree of their social danger, which makes it possible to study the reasons and develop a scientifically substantiated concept of measures to prevent them. Based on the materials of criminological characteristics, the authors aimed to analyze the current experience and role of the National Police in preventing the investigated group of crimes in order to develop scientifically sound recommendations and amend existing regulations of Ukraine. A compulsory aspect of the effective introduction of new technologies for public order is a continuous improvement of qualifications and practical skills among the employees of the National Police of Ukraine. According to the results of the study, the purpose of improving the activities of the National Police of Ukraine is proposed to use the Scandinavian experience of public safety, which includes de-escalation, prevention of violence through constant communication with the crowd, careful planning and risk analysis, expanding the range of new technologies used by the National Police including face recognition, use of drones, computer prediction of criminal offenses, further expansion of the list of settlements with the successful implementation of the project "Safe City".

Выработаны научно обоснованные рекомендации по предотвращению преступлений против общественного порядка силами Национальной полиции Украины. Исследованы количественно-качественные показатели преступлений против общественного порядка за последнее десятилетие. Проанализированы действующие международные и отечественные нормативно правовые акты, материалы имеющихся научных исследований. Рассмотрены положения, касающиеся предотвращения преступлений против общественного порядка, даны рекомендации по усовершенствованию нормативно-правового регулирования.
Crimes against public order: criminological characteristics and National Police of Ukraine prevention issues
Денисов, С. Ф. Злочини проти громадського порядку: кримінологічна характеристика та питання запобігання Національною поліцією України / Денисов Сергій Федорович, Заїка Дмитро Євгенійович // Українська поліцеїстика: теорія, законодавство, практика. - 2022. - № 1(3). - С. 99-115. - DOI: https://doi.org/10.32366/2709-9261-2022-3-1-99-115.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; злочини проти громадського порядку; crimes against public order; преступления против общественного порядка; кримінологічна характеристика; criminological characteristics; криминологическая характеристика; громадський порядок; public order; общественный порядок; особа злочинця; person of the criminal; личность преступника; запобігання злочинності; crime prevention; предотвращение преступности